Pump–probe capabilities at the SPB/SFX instrument of the European XFEL. (21st July 2022) - Koliyadu, Jayanath C. P.; Letrun, Romain; Kirkwood, Henry J.; Liu, Jia; Jiang, Man; Emons, Moritz; Bean, Richard; Bellucci, Valerio; Bielecki, Johan; Birnsteinova, Sarlota; de Wijn, Raphael; Dietze, Thomas; et al.
Abstract : The pump–probe capabilities at the SPB/SFX instrument of the European XFEL are discussed. Abstract : Pump–probe experiments at X‐ray free‐electron laser (XFEL) facilities are a powerful tool for studying dynamics at ultrafast and longer timescales. Observing the dynamics in diverse scientific cases requires optical laser systems with a wide range of wavelength, flexible pulse sequences and different pulse durations, especially in the pump source. Here, the pump–probe instrumentation available for measurements at the Single Particles, Clusters, and Biomolecules and Serial Femtosecond Crystallography (SPB/SFX) instrument of the European XFEL is reported. The temporal and spatial stability of this instrumentation is also presented.